Kepastian Hukum Batas Waktu Pengajuan Peninjauan Kembali dalam Perkara Perdata Pasca Putusan Mahkamah Konstitusi dan Penerapannya di Pengadilan - M. Naufal Afif; M. Naufal Nabil Wijaya; Achmad Mahatir; Mesya Assauma Nurfitrah (Judge : Jurnal Hukum, 2026)
Judicial Review (PK) is an extraordinary legal remedy in Indonesian civil procedure, designed to provide correction against final and binding court decisions. The submission deadline for PK remains a highly debated issue, as it underscores the balance between legal certainty and substantive justice. This study uses a normative juridical methodology, integrating statutory and conceptual perspectives, and examines Constitutional Court Decision No. 108/PUU-XIV/2016 as its focal point. The findings reveal that prior to the Constitutional Court’s intervention, the 180-day time limit stipulated in Article 69 of the Supreme Court Law was frequently subject to ambiguous interpretation, particularly regarding the starting point of calculation and the possibility of repeated PK submissions. Following the Constitutional Court’s ruling, the restriction of PK to a single submission within 180 days was affirmed as constitutional, thereby reinforcing the principle of legal certainty and the finality of judgments (lites finiri oportet). This decision shifted judicial practice from a flexible-substantive approach to a more formal-positivistic one, while still safeguarding the constitutional rights of justice seekers. Consequently, this research contributes to strengthening legal certainty in Indonesian civil procedural law without disregarding substantive justice.